1993
DOI: 10.1021/bi00066a005
|View full text |Cite
|
Sign up to set email alerts
|

Subunit interactions provide a significant contribution to the stability of the dimeric four-.alpha.-helical-bundle protein ROP

Abstract: Detailed thermodynamic and spectroscopic studies were carried out on the ColE1-ROP protein in order to establish a quantitative basis for the contribution of noncovalent interactions to the stability of four-helix-bundle proteins. The energetics of both heat- and GdnHCl-induced denaturation were measured by differential scanning microcalorimetry (DSC) and/or by following the change in circular dichroism in the far-UV range. Sedimentation equilibrium analyses were performed to characterize the state of aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 40 publications
(40 reference statements)
7
68
1
Order By: Relevance
“…See Table 2. We should note that our results for wild-type Ropl 1 are in fair agreement with those published by Steif et al (1993), who used a buffer of much lower ionic strength than we did. The greatest difference is in ACD, which, as mentioned above, when eval- matic difference in the rates of folding and unfolding of the wild-type and repacked proteins suggests that the hydrophobic core of Rop plays a critical role in the rate-determining step of folding.…”
Section: Munson Et Alsupporting
confidence: 93%
See 1 more Smart Citation
“…See Table 2. We should note that our results for wild-type Ropl 1 are in fair agreement with those published by Steif et al (1993), who used a buffer of much lower ionic strength than we did. The greatest difference is in ACD, which, as mentioned above, when eval- matic difference in the rates of folding and unfolding of the wild-type and repacked proteins suggests that the hydrophobic core of Rop plays a critical role in the rate-determining step of folding.…”
Section: Munson Et Alsupporting
confidence: 93%
“…This observation provides an explanation for the results of Steif et al (1993), who reported, using 24-h equilibration times, that there was hysteresis between the GuHC1-induced folding and unfolding curves for wild-type Rop. They reported the midpoint of the unfolding transition as approximately 5.3 M and of the folding as approximately 2.5 M, at 19 "C with protein concentrations of 0.3 mg/mL.…”
Section: Munson Et Alsupporting
confidence: 60%
“…("""_) , and monomer-dimer (----) equilibrium schemes 'Steif et al (1993) ' Chmielewski and Lipton (1994) ..…”
Section: Resultsmentioning
confidence: 99%
“…The integrated calorimetric unfolding enthalpy (∆H Cal ) for Zwit-1F is 7.2 cal‚g -1 , within the range observed for natural globular proteins (5.2-11.8 cal‚g -1 ), 19,20 but somewhat lower than GCN4 (7.7 cal‚g -1 ) 21 and ROP (9.5 cal‚g -1 ). 17 The NMR spectra of many well-folded natural and designed proteins are characterized by differentiated amide resonances and slow hydrogen/deuterium exchange. 22 The amide N-H resonances in the 1 H spectrum of Zwit-1F, under conditions where the sample is 97% octameric, span 1.4 ppm ( Figure 3A).…”
mentioning
confidence: 99%